Physics for Cambridge International AS & A level - Sang, David; Jones Graham, Chadha Gurinder & Woodside Richard (London Cambridge University Press, 2020)
he coursebook provides a range of enquiry questions such as practical activities, group work and debate questions that develop 21st century skills. This resource is written to support English as a second language learners with key command terms, key words, accessible language throughout and glossary definitions in context throughout the text. The coursebook is part of a flexible suite of resources revised for examination from 2022. The series provides activities to develop and enhance students' investigative skills, with a step-by-step approach tailored to syllabus objectives. The resources offer a large variety of active lesson ideas and practical support, which helps with differentiation and reflection
1. Kinematics 2.Accelerated motion 3.Dynamics 4.Forces 5.Work, energy and power 6.Momentum 7.Matter and materials 8.Electric current 9.Kirchhoff's laws 10.Resistance and resistivityy 11.Practical circuits 12.Waves 13.Superposition of waves 14.Stationary waves 15.Atomic structure P1.Practical skills at AS level 16.Circular motion 17.Gravitational fields 18.Oscillations 19.Thermal physics 20.Ideal gases 21.Uniform electric fields 22.Coulomb's law 23.Capacitance 24.Magnetic fields and electromagnetism 25.Motion of charged particles 26.Electromagnetic induction 27.Alternating currents 28.Quantum physics 29.Nuclear physics 30.Medical imaging 31.Astronomy and cosmology P2.Practical skills at A Level
Keywords: Physics, textbook, Excercise